Social Life in Willa Cather’s One of Ours : Social Life in Willa Cather’s One of Ours - Ali, Muhammad Ilham (Universitas Mulawarman, 2023)
This article determining the interpretation of the quotation in Willa Cather’s One of Ours focused on social situations and conditions. In conducting the research, the writer uses qualitative research because the data was collected in the form of words, quotations from the novel, and several sources that support the research. Through a sociological approach, the analysis focused on the social situation in the novel itself. The result of the study is the interpretation of social life on a farm and ranch; social life in religion or spiritual; social life including romance and marriage; social life during the influenza plague’s outbreak; social life during war; and the writer adds the social life on studying at the university, the situation in the train, the situation on the ship and situation in the military that the main character experiences.